Creating a Sharia-Based School: the Relationship Between Madrasah Leadership and Teacher Discipline With the Effectiveness Of Educational Management - Dedi Muliadi; Syaibatul Aslamiyah; Mega Mesra Resmi; Yayan Sopyan; Arskal Salim; Syahrullah (Jurnal At-Tarbiyat: Jurnal Pendidikan Islam, 2025)
The implementation of Islamic legal values in education management is an urgent issue in strengthening the quality of Islamic-based schools. This study aims to analyze the influence of the leadership of the madrasah head and teacher work discipline on the effectiveness of implementing Islamic legal values at MTs Nurul Huda Jakarta. Using a quantitative approach with survey design, data were collected from 60 teachers through questionnaires and analyzed using multiple regression. The results show that both leadership and work discipline significantly affect the implementation of Islamic legal values, with teacher discipline having a stronger influence (β = 0.6581) than leadership (β = 0.4509). Together, both variables explain 65.8% of the variance (R² = 0.658), indicating that the research hypotheses are accepted. These findings strengthen the theoretical perspective that effective leadership and consistent teacher discipline are critical in realizing Sharia-based education management. Academically, this research contributes empirical evidence to the field of Islamic education management, while practically, it provides insights for improving leadership strategies, teacher professionalism, and policy support for value-based schools.